2013
DOI: 10.1364/ol.38.001999
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and broad wavelength sweeping of standard telecommunication distributed feedback laser diode

Abstract: This Letter presents a method for the fast and broad wavelength sweeping of a standard setup of a diode's active region and its immediate vicinity, which contain the diode's optical feedback system. The selective and rapid heating of the active region is possible due to the confinement of the voltage drop to the active diode's region that has submicrometer thickness. Using the presented method and an off-the-shelf telecommunication distributed feedback laser diode, we demonstrate wavelength sweeps in excess of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A particularly suitable and highly cost-efficient swept laser source, which can accommodate the requirements presented by theoretical modeling, was obtained using a standard Telecom DFB laser diode driven by unusually high-amplitude and short-duration current pulses. This method was studied in detail in [ 7 ]. The method utilizes selective and very rapid temperature cycling of the DFB laser diode’s active region.…”
Section: The Ofs Signal Generatormentioning
confidence: 99%
See 2 more Smart Citations
“…A particularly suitable and highly cost-efficient swept laser source, which can accommodate the requirements presented by theoretical modeling, was obtained using a standard Telecom DFB laser diode driven by unusually high-amplitude and short-duration current pulses. This method was studied in detail in [ 7 ]. The method utilizes selective and very rapid temperature cycling of the DFB laser diode’s active region.…”
Section: The Ofs Signal Generatormentioning
confidence: 99%
“…However, the PZT fiber stretcher would be impractical for tuning the generated frequency with the proposed THz signal generator since the PZT fiber stretcher can stretch the fiber only for few millimeters with a fiber length of several meters [ 6 ]. The authors of [ 7 ] proposed a fast OFS of a standard telecommunication DFB laser diode with a selective and rapid temperature cycling of the DFB laser diode’s active region. The DFB laser diode’s active region was heated using a current pulse with a high amplitude and short duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Sanders for rapid wavelength tuning. [70, 71] This tuning method also has the potential for scanning over many transitions rapidly (< 1 ms). The resulting spectra could be analyzed with a multi-spectrum fit [72] where each transition is fit together in order to determine the pressure and temperature.…”
Section: 1 Conclusionmentioning
confidence: 99%
“…[3] By applying a 2 ampere 250 ns duration current pulse directly to the DFB Njegovec et al has demonstrated wavelength tuning on the order of 50 cm −1 in 250 ns with a 10 kHz repetition rate. [4] The wavelength tuning is driven by internal heating of the substrate due to Joule heating.…”
Section: Introductionmentioning
confidence: 99%